Analisis Hasil Observasi dan Supervisi - Fajar Nurrohman (Ar-Rosikhun: Jurnal Manajemen Pendidikan Islam, 2021)
This study aimed to describe the steps taken by principals and supervisors in analyzing the results of observations and supervision. Principals and supervisors must have skills in analyzing and compiling reports on the implementation of supervision based on data, objective facts as an independent work area in the education system. This research is a library research using content analysis method. In carrying out the analysis of the results of observation and supervision, principals and supervisors refer to: the results of learning planning, learning implementation and learning assessment results. The next step taken by the Principal and Supervisor is to compile a supervision report which is used as a document containing notes about the work carried out by the principal and supervisor. In preparing the supervision report, it is necessary for the principal and supervisor to pay attention to the aspects that must be included in the content of the supervision report.